2005
DOI: 10.1103/physrevb.72.115338
|View full text |Cite
|
Sign up to set email alerts
|

Coupling atomistic and continuum length scales in heteroepitaxial systems: Multiscale molecular-dynamics/finite-element simulations of strain relaxation inSiSi3N4nanopixels

Abstract: A hybrid atomistic-continuum simulation approach has been implemented to study strain relaxation in lattice-mismatched Si/ Si 3 N 4 nanopixels on a Si͑111͒ substrate. We couple the molecular-dynamics ͑MD͒ and finite-element simulation approaches to provide an atomistic description near the interface and a continuum description deep into the substrate, increasing the accessible length scales and greatly reducing the computational cost. The results of the hybrid simulation are validated against full multimillion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Lidorikis et al [12] reported a hybrid atomisticcontinuum simulation approach, implemented to study strain relaxation in lattice-mismatched Si/Si 3 N 4 nanopixels on a Si(1 1 1) substrate. They coupled the MD and macro-scale finite-element simulation approaches to provide an atomistic description near the interface and a continuum description deep into the substrate, thereby, increasing the accessible length scales and significantly reducing the computational cost.…”
Section: Introductionmentioning
confidence: 99%
“…Lidorikis et al [12] reported a hybrid atomisticcontinuum simulation approach, implemented to study strain relaxation in lattice-mismatched Si/Si 3 N 4 nanopixels on a Si(1 1 1) substrate. They coupled the MD and macro-scale finite-element simulation approaches to provide an atomistic description near the interface and a continuum description deep into the substrate, thereby, increasing the accessible length scales and significantly reducing the computational cost.…”
Section: Introductionmentioning
confidence: 99%
“…The nitrogen atom is then bonded to three Si atoms across the interface with a bond length around 2.5 Å. It has been found that successive D1 -> D2 and D2 -> D1 slips relax the mismatch strain in form of a triangular superlattice of interfacial domains [Lidorikis et al, 2005]. In the simulation presented here the initial configuration was in phase D1.…”
Section: Pair Distribution Functions In Bulk Silicon Nitridementioning
confidence: 90%
“…After that, because the center piece is disconnected from the region on the left and the right that is being pulled, it can relax to almost the unstrained configuration which is reflected in the fact that the peak height of the first peak returns almost to its original value. Two different coherent interface phases leading to a local energy minimum configuration have been considered earlier [Lidorikis et al, 2005]. The phase D1 consists of the N atoms of type 4 in the interface plane of silicon nitride being positioned directly on top of the Si atoms of type 8 in the interface double layer of silicon (see figure 13.a)) with a bond length of 1.75 Å.…”
Section: Pair Distribution Functions In Bulk Silicon Nitridementioning
confidence: 99%